Immune Thrombocytopenia (ITP) Secondary to Subclinical Hashimoto's Thyroiditis - Hassan Tahir MD; Faizan Sheraz MD; Jahnavi Sagi MD; Vistasp Daruwalla MD (SAGE Publishing, 2016)
Immune thrombocytopenia (ITP) is the most common cause of isolated thrombocytopenia in healthy people. ITP may rarely coexist with autoimmune thyroid disorders, which may indicate more complex defect in immune system. Primary ITP usually responds well to steroids and intravenous immunoglobulins. However, ITP may be difficult to treat when associated with thyroid autoimmune disorders. In such cases, treating the underlying thyroid disorder may significantly improve platelet count and can either cause remission of disease or improve response to standard ITP therapy. We report a case of 47-year-old male who was diagnosed with ITP and was also found to have subclinical Hashimoto's thyroiditis. Treatment of subclinical hypothyroidism with levothyroxine in our patient significantly improved the platelets, thus successfully bringing the disease in remission.